(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
At present, one of the universal problems, one of the threats to international security and progress is the globalization of ideological processes and the struggle against it, reducing its influence and ensuring the information security of the regions of the world. This problem in its scope and threats far exceeds the scale of terrorism, ethnic and religious conflicts, racism and other security threats.